Synthesis and utility of new amine/nucleobase addition products of allenylphosphonates - Swamy, K. C. Kumara; Balaraman, Ekambaram; Kumar, N. Satish (Tetrahedron, 2006)
In the reaction of allenylphosphonates with amines/nucleobases, depending on the amine and the allenylphosphonate, either Z- or E-vinylphosphonate or allylphosphonate as a single isomer with a β-amino functionality was isolated. A simple route to phosphonates with a β-NH2 group is developed by direct reaction with ammonia. In reactions with adenine, three different modes of reaction, with one of them involving an unusual cyclisation, are observed. The utility of (enamino)allyl phosphonate products thus obtained in the synthesis of (enamino)-1,3-butadienes via Horner–Wadsworth–Emmons (HWE) reaction is also demonstrated.

Synthesis of peptides and pyrazines from beta-aminoalcohols via extrusion of H2 catalyzed by ruthenium pincer complexes. ligand controlled selectivity - Gnanaprakasam, Boopathy; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Angewandte Chemie, 2011)
Bitte wählen: Die Wahl des Katalysators, eines Ru-Pinzettenkomplexes, bestimmt, ob Peptide oder Pyrazine aus β-Aminoalkoholen entstehen: Der PNN-Komplex 1 führt, je nach Substituent R (siehe Schema), zu linearem Polyalanin oder zu cyclischen Dipeptiden, der PNP-Komplex 2 katalysiert die Bildung von Pyrazinen. Die Reaktionen finden in homogener Lösung unter neutralen Bedingungen statt.

Synthesis of polyamides from diols and diamines with liberation of H2 - Gnanaprakasam, Boopathy; Balaraman, Ekambaram; Gunanathan, Chidambaram; Milstein, David (Journal of Polymer Science Part A: Polymer Chemistry, 2012)
The amidation reaction based on catalytic coupling of alcohols with amines previously reported by us, using the pincer complexes 1 and 2 as catalysts, was applied to the generation of polyamides from nonactivated diols and diamines. A range of polymers was prepared, with Mn up to 26.9 kDa. Unlike the traditional syntheses of polyamides based on carboxylic acid derivatives, which require the use of toxic reagents and generate stoichiometric amounts of waste, this process generates only molecular hydrogen as byproduct. Both aromatic and aliphatic diols and diamines were used. Gel permeation chromatography measurements of the dimethylformamide-soluble polymers and thermal studies of the polyamides were performed. Matrix assisted laser desorption/ionization time-of-flight (MALDI-TOF) spectra are also reported. Thermogravimetric analyses studies indicate that the aromatic polyamides (with the exception of the pyridine-based polyamide) are more thermally stable than the aliphatic ones. This general, environmentally benign method for the synthesis of polyamides is homogeneously catalyzed under neutral conditions by dearomatized ruthenium-pincer complexes 1 and 2 and proceeds in 1,4-dioxane under an inert atmosphere. Conditions for polyamidation in the absence of solvent are also reported, using the pincer complex 2 as catalyst. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2012

Stepwise metal-ligand cooperation via a reversible aromatization-deconjugation-sequence in ruthenium complexes with a tetradentate phenanthroline-based ligand - Langer, Robert; Fuchs, Ido; Vogt, Matthias; Balaraman, Ekambaram; Diskin-Posner, Yael; Shimon, Linda J. W.; Ben-David, Yehoshoa; Milstein, David (Chemistry - A European Journal, 2013)
The synthesis and reactivity of ruthenium complexes containing the tetradentate phenanthroline-based phosphine ligand 2,9-bis((di-tert-butylphosphino)methyl)-1,10-phenanthroline (PPhenP) is described. The hydrido chloro complex [RuHCl(PPhenP)] (2) undergoes facile dearomatization upon deprotonation of the benzylic position, to give [RuH(PPhenP-H)] (4). Addition of dihydrogen to 4 causes rearomatization of the phenanthroline moiety to trans-[Ru(H)2(PPhenP)] (5), followed by hydrogenation of an aromatic heterocycle in the ligand backbone, to give a new dearomatized and deconjugated complex [RuH(PPhenP*-H)] (6). These aromatization/deconjugation steps of the coordinated ligand were demonstrated to be reversible and operative in the dehydrogenation of primary alcohols without the need for a hydrogen acceptor. This aromatization/deconjugation sequence constitutes an unprecedented mode of a stepwise cooperation between the metal center and the coordinated ligand.

Synthesis, structures, and dearomatization by deprotonation of iron complexes featuring bipyridine-based PNN pincer ligands - Zell, Thomas; Langer, Robert; Iron, Mark A.; Konstantinovski, Leonid; Shimon, Linda J. W.; Diskin-Posner, Yael; Leitus, Gregory; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Inorganic Chemistry, 2013)
The synthesis and characterization of new iron pincer complexes bearing bipyridine-based PNN ligands is reported. Three phosphine-substituted pincer ligands, namely, the known tBu-PNN (6-((di-tert-butylphosphino)methyl)-2,2′-bipyridine) and the two new iPr-PNN (6-((di-iso-propylphosphino)methyl)-2,2′-bipyridine) and Ph-PNN (6-((diphenylphosphino)methyl)-2,2′-bipyridine) ligands were synthesized and studied in ligation reactions with iron(II) chloride and bromide. These reactions lead to the formation of two types of complexes: mono-chelated neutral complexes of the type [(R-PNN)Fe(X)2] and bis-chelated dicationic complexes of the type [(R-PNN)2Fe]2+. The complexes [(R-PNN)Fe(X)2] (1: R = tBu, X = Cl, 2: R = tBu, X = Br, 3: R = iPr, X = Cl, and 4: R = iPr, X = Br) are readily prepared from reactions of FeX2 with the free R-PNN ligand in a 1:1 ratio. Magnetic susceptibility measurements show that these complexes have a high-spin ground state (S = 2) at room temperature. Employing a 2-fold or higher excess of iPr-PNN, diamagnetic hexacoordinated dicationic complexes of the type [(iPr-PNN)2Fe](X)2 (5: X = Cl, and 6: X = Br) are formed. The reactions of Ph-PNN with FeX2 in a 1:1 ratio lead to similar complexes of the type [(Ph-PNN)2Fe](FeX4) (7: X = Cl, and 8: X = Br). Single crystal X-ray studies of 1, 2, 4, 6, and 8 do not indicate electron transfer from the FeII centers to the neutral bipyridine unit based on the determined bond lengths. Density functional theory (DFT) calculations were performed to compare the relative energies of the mono- and bis-chelated complexes. The doubly deprotonated complexes [(R-PNN*)2Fe] (9: R = iPr, and 10: R = Ph) were synthesized by reactions of the dicationic complexes 6 and 8 with KOtBu. The dearomatized nature of the central pyridine of the pincer ligand was established by X-ray diffraction analysis of single crystals of 10. Reactivity studies show that 9 and 10 have a slightly different behavior in protonation reactions.

Sustainable Iron-catalyzed direct imine formation by acceptorless dehydrogenative coupling of alcohols with amines - Jaiswal, Garima; Landge, Vinod Gokulkrishna; Jagadeesan, Dinesh; Balaraman, Ekambaram (Green Chemistry, 2016)
The Acceptorless Dehydrogenative Coupling (ADC) of alcohols with amines is reported using a heterogeneous Fe-catalyst. The reaction operates under mild conditions with the liberation of dihydrogen and water as the byproducts. The developed ADC strategy is simple, efficient, exhibits wide functional group tolerance and can be scaled up. The present catalytic approach possesses a dual role; acting as a catalyst as well as being magnetically separable. The sustainable reuse of a heterogeneous iron catalyst is also shown.

Simple cobalt(II) chloride catalyzed N-alkylation of amines with alcohols - Midya, Siba P.; Mondal, Akash; Begum, Ayesha; Balaraman, Ekambaram (Synthesis-Stuttgart, 2017)
A facile cobalt-catalyzed N-alkylation of amines with alcohols using inexpensive, commercially available CoCl2 center dot 6H(2)O is reported. Employing this readily available cobalt catalyst, a variety of amines with wide functional group tolerance were selectively alkylated under benign conditions.
Keywords: (Hetero)Aromatic Amines; Alcohols; Amination; amines; Anilines; Aromatic-amines; Cobalt Catalysis; Dehydrogenation Borrowing Hydrogen; Efficient Catalysts; Hydrogen Autotransfer; Iridium; N-alkylation; Pincer-complex; Secondary Alcohols; Selective Alkylation